Chromobacterium violaceum – an unusual pathogen. Perspectives to ponder!! (Eastern Journal of Medical Sciences, 2018)
Human infection due to Chromobacterium violaceum is rare, even though the bacteria are ubiquitous in distribution. Without appropriate antimicrobial therapy, the consequences can be rapidly fatal if septicemia sets in. Both pigmented and nonpigmented varieties are equally virulent. Mortality rates are quite high despite treatment. The history of trauma and simultaneous exposure to water and soil should alert clinician about this entity. Fluoroquinolones and aminoglycosides show good sensitivity, whereas penicillin and early cephalosporins are poor therapeutic options. Treatment for an extended period beyond clinical cure is indispensable to prevent relapse. Combination of prompt diagnosis, optimal antimicrobial therapy, and adequate therapeutic duration for C. violaceum infection is the key for successful therapy. We present here two cases of C. violaceum infections with interesting presentations with a brief review of literature.